Clinical Features of Spontaneous Regression of Retinopathy of Prematurity in China: A 5-Year Retrospective Case Series - Wang, Liang; Li, Manhong; Zhu, Jun; Yan, Hongxiang; Wu, Lei; Fan, Jing; Zhou, Yi; Gou, Kaili; Zhang, Zifeng; Wang, Yusheng (Frontiers in Medicine, 2021)
Purpose: The aim of this study is to explore the clinical features of spontaneous regression of retinopathy of prematurity (ROP) in China, including fundus appearance, time course and affecting factors. Methods: Data of paediatric patients in whom ROP spontaneously regressed without treatment were collected, including general demographics, medical history, zones and stages of ROP, and changes of fundus appearance. The fundus manifestations of spontaneous regression in ROP were systematically summarized. Meanwhile, the time course of spontaneous regression in ROP was further analysed, including the onset time, completion time, and duration of regression, which were all compared across different ROP zones and stages. The associated factors were analysed by survival analysis for their correlation with delayed regression for the first time. Results: Two hundred and thirty-seven eyes of 237 paediatric patients were included. The fundus manifestations of regression differed across stages. Lesions gradually subsided and the retinal vessels gradually vascularized completely. However, despite ROP regression, some abnormalities remained. We observed avascular retina in the temporal periphery (19.0%), increased vascular branching (6.8%), retinal pigmentary changes (6.8%), and smaller angle between upper and lower temporal retinal vessel trunks (3.0%). Acute ROP started to regress at a median 40 weeks of postmenstrual age (PMA), and completely regressed by median 49.0 weeks of PMA. The median duration for regression was 8.5 weeks. The zone Ⅱ ROP and stage 3 ROP had a later time for onset and completion of regression, and longer duration. Anemia and retinal hemorrhage (RH) were identified as independent risk factors for delayed regression by survival analysis. Conclusions: During spontaneous regression, the fundus appearance are diverse and the retinal vessels gradually vascularized completely. The time course of regression differs depending on the ROP zone and stage. Anemia and RH are independent risk factors for delayed regression. Further research of the natural course of the regression of ROP is needed to help design effective screening and follow-up plans.